Validating the utility of the Kestenbaum number in various types of optic atrophy - Madhurima A. Nayak; Sagar Agarwal; Akshata Charlotte; Krishna Vaitheeswaran; N. Srikant (Journal of Clinical Ophthalmology and Research)
Background: Kestenbaum number (KN) is the count of capillaries on the optic disc surface and a number <6 denotes optic atrophy (OA). Materials and Methods: This prospective cross-sectional study included 35 cases of OA who underwent a comprehensive ophthalmic examination, calculation of the KN following fundus photography, visual field analysis, and optical coherence tomography (OCT). Visual acuity was recorded as a logarithm of minimum angle of resolution (logMAR). The data were analyzed using one-way analysis of variance and Pearson correlation. Results: Sixty three eyes of 35 patients had optic atrophy. The average age of presentation was 47.37 ± 13.34 years. Primary OA was the most common morphological type of OA, and pituitary tumor was the most common cause of the same. The differences in average age, logMAR, grade of disc pallor, and KN among various types of OA were not statistically significant. There was a statistically significant negative correlation between KN and logMAR and the grade of disc pallor. Furthermore, KN correlated well with retinal nerve fiber layer thickness and ganglion cell thickness by OCT. There was no significant correlation between KN and visual field parameters. Conclusion: KN is a reliable indicator of the grade of OA. However, it does not aid in differentiating morphological types of OA.